Peran Guru dalam Mengembangkan Kemampuan Bicara Anak dengan Speech Delay melalui Media Pembelajaran Visual dan Strategi Interaktif - Anriyani, Liza; Wulansari Vitaloka (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to analyze the role of teachers in developing speech skills of children with speech delay through the use of visual learning media and interactive strategies at RA Amanah Bunda. The research method used a qualitative approach with a case study design, involving observation, in-depth interviews, and documentation of teachers who handle children with speech delay. The results of the study show that the main factors of speech delay in children are genetic factors (40%), lack of language stimulation at home (35%), and a less supportive social environment (25%). Interventions included the use of media such as pictures, videos, word cards and educational games, which were shown to increase children's vocabulary by 85% and articulation understanding by 75%. Strategies such as word repetition, responsive communication and habituation of verbal interactions improved children's speech by 45% in one month and speech fluency by 60% in two months. In addition, active collaboration between teachers and parents contributed to 70% of children being able to use simple sentences independently and 85% of children experiencing increased confidence in communication. This research confirms that a combination of interactive media and responsive communication strategies is an effective approach in addressing speech delay in early childhood.